Optimum Doses of N, P, And K Fertilizers For Samosir Shallot Varieties in the Plains of the Lake Toba Region - Razali; Siregar, Dolly Sojuangan (Jurnal Online Pertanian Tropik, 2025)
The surrounding plain of Lake Toba is well known as a shallot producing area in North Sumatra Province. Samosir variety is the mainstay variety of shallot farmers in this area. One of the efforts to increase the productivity of shallot variety Samosir is the application of fertilizer. The amount of N, P and K nutrients given to the Samosir variety shallot plants must be appropriate. This study aims to obtain the optimum dose of N, P and K fertilizers in the cultivation of shallot varieties Samosir planted in the rainy season in the plains around Lake Toba. This study consisted of 3 parallel experiments to determine the optimum N, P, K fertilization with a non-factorial randomized group design (RAK). P2O5 and K2O fertilizers were applied 100% in the N rate experiment, N and K2O fertilizers were applied 100% in the P rate experiment, and N and P2O5 fertilizers were applied 100% in the K rate experiment. Each experiment consisted of 5 levels, namely 0, 50, 100, 150, and 200% of the reference dose and each treatment was repeated 3 times so that there were 45 experimental plots. Parameters were: fresh weight of tubers and crowns at the end of the vegetative period, crown weight and wind-dried harvest tubers. The results obtained the optimum dose of N and P fertilizer recommendations are 154.22 kg N ha-1 and 126.62 kg P2O5 ha-1. For K fertilization does not give a quadratic response pattern so there is no optimum dose.